DETERMINANTS OF SHARIA-BASED MONEY MARKETS IN INDONESIA: AN EMPIRICAL STUDY - Kurniawan, Muhammad Arif; Masyita, Dian; Anwar, Mokhamad; Nidar, Sulaeman Rahman (CENTRAL ASIA AND THE CAUCASUS, 2022)
In line with the implementation of law 21 of 2008, the Government must regulate sharia bank operations in detail and comprehensively. This study aims to explain the interbank money market model based on sharia principles in the Indonesian context. The mixed method of quantitative and descriptive causality is employed to describe the influence of the sharia money market phenomenon that occurs. Observation of cross- sectional time series data was performed in one specific time period, namely data from 2009 to 2020 using Eviews 9 software. Autoregressive Distributed Lag (ARDL) analysis was used as the basis for using the Ordinary Least Square (OLS) model so that stationarity tests were required on each variable using the Unit Root Test. The results showed that the volume of PUAS, interbank mudharabah investment, sharia SBI, GWM, deposit, financing, operation cost, ROA and exchange rate are the variables that shape the determinant of the sharia money market in Indonesia. This model is completely free from the problems of heteroskedastisitas, autocorrelation and multicollinearity and therefore it was used to generate a solution in the form of a model that can provide the best predictive results.